+0  
 
+3
47
1
avatar+1674 

How do you multiply the expressions with the imaginary number i? I'm confused!

 Feb 18, 2019
 #1
avatar+98126 
+3

Remember that    i * i  =  i^2 = -1

 

a)   (-4i) ( 6i) = -4 * 6 * i * i    =  -24 * -1   =  24

 

b (2 + i) ( 2 - i)  = 

(2 + i) * 2    -  (2 + i)*i   =

4+ 2i - 2i - i^2  =

4 - i^2

4 - (-1) =

5

 

c)  ( 4 - 3i) ( 5 + i) =

(4 - 3i) * 5  + (4 - 3i) * i  =

20 - 15i + 4i - 3i^2 =

20 - 11i - 3(-1) =

23 - 11i

 

 

cool cool cool

 Feb 18, 2019

18 Online Users